Upaya Pencegahan Kerugian pada Kreditur yang Dilakukan Debitur dalam Kepailitan - Deshy Eka Permatasari; Kefianto K; Aisyah Nurhaliza; Nabila Zalfa; Muhammad Prima Adiguna (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Actio Pauliana is a legal action allowing a bankruptcy curator to annul transactions harming creditors, aiming to prevent unfair asset transfers and safeguard creditors' interests. The research method is juridical normative with a statute approach and case approach. It refers to Putusan No. 6/Pdt. Sus-Pailit/2018/PN.Niaga.Medan and Putusan Mahkamah Agung Nomor 560 K/Pdt.Sus-Pailit/2021 as the main discussion sources. The outcome is that PT. Bina Karya Sarana must pay all debts of petitioning creditors using the debtor's assets as collateral, After bankruptcy verdict, all debtor's assets become public seizure based on the judge's considerations during the trial. The Supreme Court Verdict No. 560 K/Pdt.Sus-Pailit/2021 concludes from the study that actio pauliana doesn't meet the "other matters" element in the Bankruptcy Law. However, the actio pauliana lawsuit criteria, as per Bankruptcy Law No. 37 of 2004, are fulfilled.